Thirteen days to midnight - Carman, Patrick (Little, Brown and Co., 2011)
When Jacob shares about his indestructible power with two of his friends, they decide to use his power for good and save others. But they soon discover that good intentions aren't always followed by positive outcomes. Jacob learns there is a dark side to his power, and he has only thirteen days to figure out how to capture and destroy it.